Respond, Recovery, and Renew Strategies in Strengthening Competitiveness of Cooperatives After COVID-19 Pandemic in West Java - Risris Rismayani; Ratri Wahyuningtyas; Ganjar Disastra (Binus Business Review, 2024)
The recent economic slump due to the COVID-19 pandemic causes major problems for cooperatives in West Java in maintaining their business activities. The pandemic significantly impacts the cooperatives and Small and Medium Enterprises (SMEs). Thus, developing strategies for cooperatives to recover, respond, and renew the issue becomes increasingly necessary. The research sought to contribute by developing alternative strategy recommendations for cooperatives in West Java, Indonesia. By doing so, it generated a competitive advantage in the post-pandemic industry. The research data were obtained through two main sources. Primary data came from Focus Group Discussion (FGD) activities involving cooperative stakeholders in West Java, consisting of cooperative managers, academicians, media, and government. Secondary data were taken from previous research. The collected data were analyzed using the Strength, Weakness, Opportunity, and Threat (SWOT analysis) approach to produce strategic recommendations visualized on the SWOT Matrix and categorized into Respond, Recovery, and Renew strategies. The results show five strategy alternatives to exploit opportunities with the cooperatives’ strengths (SO strategy). Seven strategy alternatives were identified to overcome the cooperatives’ weakness with external opportunities (WT). There are six strategy alternatives to anticipate external threats using cooperatives’ strengths (ST). Last, seven strategy alternatives are found to overcome both cooperatives’ weaknesses and external threats.